On the progenitor of the Type IIb supernova 2016gkg. Issue 4 (29th November 2016) - Kilpatrick, Charles D.; Foley, Ryan J.; Abramson, Louis E.; Pan, Yen-Chen; Lu, Cicero-Xinyu; Williams, Peter; Treu, Tommaso; Siebert, Matthew R.; Fassnacht, Christopher D.; Max, Claire E.
Abstract: We present a detection in pre-explosion Hubble Space Telescope ( HST ) imaging of a point source consistent with being the progenitor star of the Type IIb supernova (SN IIb) 2016gkg. Post-explosion imaging from the Keck adaptive optics system was used to perform relative astrometry between the Keck and HST imaging. We identify a single point source in the HST images coincident with the SN position to 0.89σ. The HST photometry is consistent with the progenitor star being an A0 Ia star with T  = 9500 K and log ( L /L⊙ ) = 5.15. We find that the SN 2016gkg progenitor star appears more consistent with binary than single-star evolutionary models. In addition, early-time light-curve data from SN 2016gkg revealed a rapid rise in luminosity within ∼0.4 d of non-detection limits, consistent with models of the cooling phase after shock break-out. We use these data to determine an explosion date of 2016 September 20.15 and progenitor-star radius of log ( R / R ⊙ ) = 2.41, which agrees with photometry from the progenitor star. Our findings are also consistent with detections of other SNe IIb progenitor stars, although more luminous and bluer than most other examples.